The majesty of man the dignity of being human - Allen, Ronald Barclay (Portland, OR Multonmah, 1984)
Includes biboiographical references and indexes.
Keywords: Bible. O.T. Psalm VIII -- criticism, interpretation, etc; Man (Christian theology).